Interfacial Engineering for Quantum-Dot-Sensitized Solar Cells - Shen, Chao (2017)
Quantum-dot-sensitized solar cells (QDSCs) are promising solar-energy-conversion devices, as low-cost alternatives to the prevailing photovoltaic technologies. Compared with molecular dyes, nanocrystalline quantum dot (QD) light absorbers exhibit higher molar extinction coefficients and a tunable photoresponse. However, the power-conversion efficiencies (PCEs) of QDSCs are generally below 9.5 %, far behind their molecular sensitizer counterparts (up to 13 %). These low PCEs have been attributed to a large free-energy loss during sensitizer regeneration, energy loss during the charge-carrier transport and transfer processes, and inefficient charge separation at the QD/electrolyte interfaces, and various interfacial engineering strategies for enhancing the PCE and cell stability have been reported. Herein, we review recent progress in the interfacial engineering of QDSCs and discuss future prospects for the development of highly efficient and stable QDSCs.